STOCK MONITORING SYSTEM DESIGN AND IMPLEMENTATION USING LOAD CELL - Prayogo, Adhie; Habiba, Curie (Universitas Muria Kudus, 2025)
This study aims to investigate the possibility of implementing the load cell to automatically monitor the inventory stock level. The study involved accuracy, repeatability and linearity testing of the sensor in measuring the weight of the loaded items which then translated into the number. Results shows that the model successfully counts the dynamic stock level loaded onto the shelf and record the timestamps of stock changes during a period of time. On the aspect of weight measurement, there are slight error observed during the experiment, ranging from 1% to 7%. However, the error number is not merely enough for consideration, especially that the nature light weight of the object, that is only 5.5 grams. This study presents a new approach to test the system by presenting the accuracy, repeatability and linearity test. Besides, the system is meant to be attached on the shelf for calculating the actual inventory level, unlike the other study which use the loadcell for frontline stock measurement mechanism. Furthermore, this study successfully provides a real-time inventory system which able to record the timestamp everytime there is a change on the stock level, unlike the other study which only informs during minimum or maximum limit. With those findings, the study enrich the discussion of using this IoT system for stock monitoring.